Następstwa reformy ekonomicznej Ksawerego Druckiego-Lubeckiego w kontekście staszicowskiego planu rozbudowy przemysłu żelaznego w staropolskim okręgu przemysłowym - Czmuchowski, Adam (The Economic Reform Results of Ksawery Drucki-Lubecki in The Context Of Staszic` Plan to Extend The Steel Industry in The Old Polish Industrial District, 2008)
When the Polish Kingdom was found in 1815, owning the significant scope of independence, the Old Polish District - located near Kielce started to be more important than up to now. In this time, Stanislaw Stasic became the governor of mining and domestic metallurgy and the period of social metallurgy started then. He was considered to be the father of Polish mining and metallurgy as well. Staszic` extension plan resulted in the next years through building of new industrial plants, extending of existing plants and their modernization. The plan also included the extention of iron ores and non-steel metals exploitation as well as the mining of salt & building materials. Staszic initiated building of many cobblestone roads, the flow regulation of rivers, re-building of cities (creating of local area plans), organisation of basic professional education and wealth allotment. In 1824 the Kingdom's industrial policy had been changed. Prince Ksawery Drucki-Lubecki became the successor of Stanislaw Staszic. The economic independence was the condition of political independence for the new minister: Prince Drucki-Lubecki. It meant the mobilisation of domesticwealth and gradual sale of national goods. The policy direction of Ksawery Drucki-Lubecki tended towards seperating the mining and metallurgy. It implemented the new organisation and activity rights of these two industrial branches as well. This direction influenced the existing industrial, economic and administrative infrastructure of Bobrza region - such as: the complex of industrial plants, which were operating for several centuries in changing conditions and belonged to the Old Polish Industrial District.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 164-175